Componentional Analysis of Verbs With a General Meaning “Manner of Movement” in English and Russian Languages - Anastasiya V. Hramova; Oksana G. Amirova (Развитие образования, 2020)
The article deals with problems of differentiating verb units with partially same meaning and the lexical meaning in modern dictionaries. The purpose of the research is to identify the integral and differential features of verbs with the common meaning “manner of movement” in English. Methods of research. In the process of the research the following research methods were used: descriptive method, method of opposition component analysis, associative experiment method, receptive experiment method, experimental method, contextual analysis. The object of the study are verbs: to dash, to parade, to race, to roam, to march, to shamble, to plod, to lumber, to shuffle, to stride, to stroll, to strut, to trudge, to wander. The authors of the article emphasize that the choice of these verb units is due to the fact that they are the most frequent lexemes representing the lexico-semantic group of verbs with the common meaning “manner of movement”. Research results. As a result of the lexicographic analysis it is turned out that the dictionary entries do not completely reveal the situation, and experimental analysis revealed additional components that depend on context.